Influence of Selective Dopamine Agonist Ropinirole on Conditioned Place Preference and Somatic Signs of Morphine Withdrawal in Rats - Shahzadi, Andleeb; Yunusoglu, Oruc; Karabulut, Enes; Sonmez, Haktan; Yazici, Zeliha (Frontiers in Behavioral Neuroscience, 2022)
The underlying mechanism of dependence and rewarding effects of morphine is imperative to understand. The primary aim of this study was to investigate whether ropinirole D2/3 agonist affects the rewarding and reinforcing properties of morphine-induced conditioned place preference (CPP) and withdrawal syndromes in rats. On day one, the animals were randomly divided to conduct the pre-test. The morphine (10mg/kg, i.p.) and/or saline was administered on alternate days in an 8-day CPP session. On day 10, fifteen minutes prior to the post-conditioning test (expression), a single dose of ropinirole (1, 2, and 5 mg/kg, i.p.) was given to rats. In extinction session, ropinirole was injected daily, and CPP was extinguished by repeated testing, with intervals of three days. Finally, reinstatement was assessed by administering ropinirole (1, 2, and 5 mg/kg) 15 minutes before the morphine injection. Morphine dependence was developed by administering increasing doses of morphine (10-50 mg/kg, i.p.). To assess withdrawal symptoms, ropinirole (1, 2, and 5 mg/kg) was injected 15 minutes before naloxone (2 mg/kg, s.c.) administration. The present study confirms that ropinirole attenuates expression and reinstatement of CPP, while it precipitates the extinction of morphine-induced CPP. Naloxone-precipitated morphine withdrawal symptoms, including wet dog shakes and weight loss, were attenuated although jumping was increased by a single ropinirole injection. Thus, ropinirole was influential in attenuating expression, reducing drug seeking and weakening reinstatement via the dopaminergic system. These findings show that ropinirole might affect neuro-adaptive changes related to dependence.